2002
DOI: 10.1038/sj.bjc.6600465
|View full text |Cite
|
Sign up to set email alerts
|

Darbepoetin alfa given every 1 or 2 weeks alleviates anaemia associated with cancer chemotherapy

Abstract: In part A of this study, patients were randomised to cohorts receiving darbepoetin alfa at doses of 0.5 to 8.0 m.c.g. kg 71 wk 71 or to a control group receiving epoetin alfa at an initial dose of 150 U kg 71 three times weekly. In part B, the cohorts were darbepoetin alfa 3.0 to 9.0 m.c.g. kg 71 every 2 weeks or epoetin alfa, initial dose 40 000 U wk 71. Safety was assessed by adverse events, changes in blood pressure, and formation of antibodies to darbepoetin alfa. Efficacy was assessed by several haematolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(95 citation statements)
references
References 14 publications
5
85
1
4
Order By: Relevance
“…Once weekly dosing also provided a convenience factor for patients. For further patient convenience, ESAs with less frequent dosing regimens (i.e., administered once every 2 weeks or once every 3 weeks) were also developed [21,22]. However, higher ESA doses (60,000 -80,000 IU) are needed with this expanded time interval to maintain target Hb levels.…”
Section: Recombinant Human Epomentioning
confidence: 99%
“…Once weekly dosing also provided a convenience factor for patients. For further patient convenience, ESAs with less frequent dosing regimens (i.e., administered once every 2 weeks or once every 3 weeks) were also developed [21,22]. However, higher ESA doses (60,000 -80,000 IU) are needed with this expanded time interval to maintain target Hb levels.…”
Section: Recombinant Human Epomentioning
confidence: 99%
“…The sialic acid-containing carbohydrate of erythropoietin determines its serum half-life (Egrie et al, 1993), and darbepoetin alpha has demonstrated a two-to three-fold longer serum half-life than rHuEPO in animal models and in patients with chronic renal failure (MacDougall et al, 1999;Egrie and Browne, 2001). In cancer patients undergoing chemotherapy, darbepoetin alpha therapy increased haemoglobin concentration when administered weekly (QW), or every 2 (Q2W), 3 (Q3W), or 4 (Q4W) weeks (Hedenus et al, 2002;Kotasek et al, 2002;Glaspy et al, 2002).…”
mentioning
confidence: 99%
“…Epoetin alfa (Eprex; Ortho Biotech, Toronto, Canada) and darbepoetin alfa (Aranesp; Amgen Inc., Thousand Oaks, CA) are approved in Canada for the treatment of anemia in nonmyeloid malignancies where anemia is a result of the concomitant administration of chemotherapy. Darbepoetin alfa is a recombinant erythropoietin with a longer half-life than epoetin alfa [9], which allows for less frequent dosing with similar efficacy in terms of hemoglobin (Hb) and QoL responses [4, 10,11].…”
Section: Introductionmentioning
confidence: 99%